Using a Non-Mandatory Book Club to Develop Pre-Service Science Teachers’ Didactic Competence - Lotta Leden; Helena Andersson (Nordina: Nordic Studies in Science Education)
Science teacher education must prepare pre-service teachers for a broad variety of teaching approaches to make science more relevant to students. Previous research has suggested fiction as one approach to a broader school science. This article describes and evaluates the experiences from a development project where a non-mandatory book-club project was implemented in science teacher education. Five upper secondary pre-service science teachers took part in the book club (1 year, 4 meetings). They read three books on various science topics and discussed how the books could be used in science teaching. They shared their experiences in a focus-group interview at the end of the book club project. The result from the interview is discussed from a didactic competence perspective. In conclusion, we argue that an incorporation of fiction in science teacher education must be accompanied by pre-service teachers’ didactic analysis of different choices for teaching, and the consequences of such choices for students’ learning and participation.